PENGARUH SUHU KARAMEL TERHADAP KUALITAS KUE SARANG SEMUT - Laela Jatmiko, Fadhilah Rizki; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
Caramel Cake often experience a failure of processed, so it necessary to analyzed the possible causes of failure, one of which the temperature of the caramel. This type of research is experiment. This research was conducted on July 2016 in Workshop Culinary Art State University of Padang. The independent variable was caramel temperature and dependent variable was the quality of the Sarang Semut Cake. The type of data was primary data sourced from 30 panelists which organoleptic test format and sample. Methods used completely randomized design by three replications. Analysis of Varian was used to analyze the data, if Fcount> Ftable then continued by Duncan test. The results showed that the use of the caramel temperature had effect on color and aroma. While the quality of the volume, shape, texture and taste had no real effect. The results of data analyzed establishes the highest score each of quality; volume of 3.12(+55oC), the neatness of form 3.10(+25oC), uniformity in the form of 3.09(+25oC and +55oC), color of 3.14(+10oC), aroma 3.28(+55oC), soft texture 3,18(+55oC), a chewy 3.13(+25oC), the porous hollow large 3.16(+55oC), and the sense of 3.09(+55oC). The best result of Caramel Cake was +55oC.Keywords: Effect, Caramel Temperature, Caramel Cake and Quality